2010
DOI: 10.4097/kjae.2010.59.1.27
|View full text |Cite
|
Sign up to set email alerts
|

A clinical comparison of continuous interscalene brachial plexus block with different basal infusion rates of 0.2% ropivacaine for shoulder surgery

Abstract: BackgroundA continuous interscalene brachial plexus block is a highly effective postoperative analgesic modality after shoulder surgery. However, there is no consensus regarding the optimal basal infusion rate of ropivacaine for a continuous interscalene brachial plexus block. A prospective, double blind study was performed to compare two different basal rates of 0.2% ropivacaine for a continuous interscalene brachial plexus block after shoulder surgery.MethodsSixty-two patients receiving shoulder surgery unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…In a previous study of open shoulder surgery, continuous ISBP analgesia required a basal infusion to provide effective pain relief, with a basal infusion of 5 ml/h [ 20 21 ]. Reducing the basal infusion from 8 to 6 ml/h resulted in similar clinical efficacy in shoulder surgery with ISBPB [ 7 ]. A basal infusion of 2 ml/h resulted in postoperative pain, night awakening, and tramadol consumption after rotator cuff surgery similar to that of an infusion of 5 ml/h, and the smaller infusion decreased the frequency of side effects [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study of open shoulder surgery, continuous ISBP analgesia required a basal infusion to provide effective pain relief, with a basal infusion of 5 ml/h [ 20 21 ]. Reducing the basal infusion from 8 to 6 ml/h resulted in similar clinical efficacy in shoulder surgery with ISBPB [ 7 ]. A basal infusion of 2 ml/h resulted in postoperative pain, night awakening, and tramadol consumption after rotator cuff surgery similar to that of an infusion of 5 ml/h, and the smaller infusion decreased the frequency of side effects [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pain quality by NRS was the primary outcome variable on which sample size estimation was based. A previous study found that the NRS score on postoperative day 1 was 1.9 ± 2.0 (mean ± SD) [ 7 ]. We assumed a 20% difference in the average pain scores over a 48-hour period between the groups to be the minimum relevant difference.…”
Section: Methodsmentioning
confidence: 99%
“…[5] have shown that one shot of 30 mL 0.5% ropivacaine with a continuous infusion of 0.2% ropivacaine at 6 mL/h or 8 mL/h for BPB without general anesthesia provided similar clinical efficacy. On the basis of this result, they concluded that the basal rate should be decreased in light of the toxicity of local anesthetics.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the use of the conventional dose of ropivacaine would have increased the occurrence of adverse events, such as prolonged numbness and delayed sensory and motor recovery, even though a higher dose of ropivacaine or bupivacaine (0.5% at 30 mL) has not been reported to induce any critical events when used for BPB. [56]…”
Section: Discussionmentioning
confidence: 99%
“…Using a nerve stimulator (Stimuplex HNS12, B. Braun, Melsungen, Germany) initially set at 1.0 mA, 0.1 milliseconds, and 1 Hz, an end-hole catheter (Contiplex A, B. Braun) was inserted with a technique similar to one previously described using a sustained contraction end point of the deltoid, pectoralis, biceps, or triceps muscles at 0.6 mA. 4 Ropivacaine 0.5% 30 mL was injected through the catheter. The catheter was subcutaneously tunneled over 3 to 4 cm through an 18-gauge IV needle and was fixed to the skin with a suture.…”
Section: Methodsmentioning
confidence: 99%